Political intervention in teacher recruitment and its impact on education quality - Ade Lestari; Muhammad Sirozi; Sholihah Titin Sumanti (Himpunan Pengembang Kurikulum Indonesia, 2026)
Political interference in teacher recruitment has become a critical issue in the education sector because it can impact the quality and integrity of the education system. In many cases, the recruitment process is influenced by political interests, nepotism, and unfair selection practices, thus undermining the principle of meritocracy. This situation can lead to the selection of teachers who lack professional qualifications and competencies, ultimately impacting the quality of education and the effectiveness of the learning process. This study aims to analyze the forms of political interference in teacher recruitment and assess their impact on the quality of education. This study conducted a literature review, analyzing academic journals and prior research on political interference and teacher recruitment. The data obtained were analyzed descriptively through thematic analysis to identify key patterns and findings. The results show that political interference generally occurs through political pressure, manipulation of recruitment procedures, and bias toward certain candidates. These practices undermine teacher professionalism, reduce transparency in recruitment, and contribute to a decline in educational quality. This study concludes that a transparent, accountable, and merit-based recruitment system is crucial for minimizing political interference and improving the quality of education. Abstrak Intervensi politik dalam rekrutmen guru telah menjadi isu penting dalam sektor pendidikan karena dapat memengaruhi kualitas dan integritas sistem pendidikan. Dalam banyak kasus, proses rekrutmen dipengaruhi oleh kepentingan politik, nepotisme, dan praktik seleksi yang tidak adil sehingga melemahkan prinsip meritokrasi. Kondisi tersebut dapat menyebabkan terpilihnya guru yang tidak memenuhi kualifikasi dan kompetensi profesional, yang pada akhirnya berdampak pada kualitas pendidikan dan efektivitas proses pembelajaran. Penelitian ini bertujuan untuk menganalisis bentuk-bentuk intervensi politik dalam rekrutmen guru serta mengkaji dampaknya terhadap kualitas pendidikan. Penelitian ini menggunakan metode literature review dengan menganalisis berbagai jurnal akademik dan penelitian terdahulu yang berkaitan dengan intervensi politik dan rekrutmen guru. Data yang diperoleh dianalisis secara deskriptif melalui analisis tematik untuk mengidentifikasi pola dan temuan utama. Hasil penelitian menunjukkan bahwa intervensi politik umumnya terjadi melalui tekanan politik, manipulasi prosedur rekrutmen, dan keberpihakan terhadap kandidat tertentu. Praktik tersebut berdampak negatif terhadap profesionalisme guru, mengurangi transparansi dalam rekrutmen, dan berkontribusi terhadap menurunnya kualitas pendidikan. Penelitian ini menyimpulkan bahwa sistem rekrutmen yang transparan, akuntabel, dan berbasis merit sangat penting untuk meminimalkan intervensi politik serta meningkatkan kualitas pendidikan. Kata Kunci: intervensi politik; kualitas pendidikan; rekrutmen guru